Design and analysis of a micro-motion manipulator - Xiang, Yu (2008)
The work in this report aims to design a monolithic compliant micro manipulator that is able to provide spatial motions. The kinematics of the spatial compliant manipulator is analyzed using the pseudo rigid body model (PRBM) concept. An approximate kinematic analysis method based on Constant-Jacobian is also studied.